Morphological features of the structure of liver complexes - F. Kh. Olimkhujhaev (Peerian Journals Publishing, 2022)
In an experiment on 142 white male mongrel rats from the moment of birth to 8 months of age, various periods of postnatal ontogenesis were studied. The early postnatal period (up to 10 days) of rat liver development is characterized by the absence of lobular structure both in the subcapsular zone and in the underlying parts of the hepatic parenchyma; the presence of initial hepatic venules formed in the subcapsular zone from the fusion of several sinusoids. From the age of two weeks to the end of postnatal ontogenesis, in the liver, along with the lobules, it is possible to distinguish constantly occurring hepatic complexes, which represent a higher level of structural organization of the hepatic parenchyma than the lobule. In the process of formation of the microvascular architectonics of the organ in postnatal ontogenesis, the main thing is the formation of new structural and functional units in the subcapsular zone of the liver.
Keywords: hepatic structure; microvessels; structural features; experiment